Adaptação ao meio líquido é importante para aprendizagem da natação? Um estudo focado nos professores - Xavier Moura, Eva Lícia (2024)
We investigated whether swimming instructors consider adaptation to the aquatic environment important for learning to swim and whether they implement such adaptation with their students. A total of 24 swimming instructors participated in the study (mean age = 37±8 years; female: n = 13, 54%; male: n = 11, 46%) with an average of 10±8 years of experience. All instructors held a degree in physical education. The data collection instrument was a questionnaire (comprising both open and closed questions) administered via an online platform (Google Forms). Our primary findings indicate that the instructors possess a broad and comprehensive understanding of the concept of adaptation to the aquatic environment, with the majority associating it with the initial phase of the swimming instruction process. The instructors reported that they consider adaptation to the aquatic environment essential for learning to swim and actively incorporate it into their lessons. The main fundamentals addressed in their classes include breathing, buoyancy, and basic diving skills. The instructors believe these fundamentals are crucial for students to adapt to the aquatic environment safely and confidently. They also noted that they have the necessary resources, materials, and infrastructure, and employ different strategies for children and adults. We concluded that adaptation to the aquatic environment is regarded as fundamental by swimming instructors, and it is systematically integrated into their lessons for beginners.